Research on the application of artificial intelligence aesthetics in the cultivation of aesthetic literacy of art-normal students - He, Fanlun (International Journal of Social Sciences and Public Administration, 2024)
The aesthetic literacy of art-normal students is an important aspect of cultivating outstanding art education talents. However, the traditional aesthetic education model has problems, such as low personalization and unclear evaluation standards. Therefore, it is of great significance to study the application of artificial intelligence (AI) aesthetics in the cultivation of aesthetic literacy of art-normal students. This research uses literature review and analysis methods to systematically sort out the relevant research results and theoretical foundations of artificial intelligence aesthetics and the cultivation of aesthetic literacy of art-normal students and discusses the application methods of artificial intelligence aesthetics in the aesthetic cultivation of art-normal students. The research has found that artificial intelligence aesthetics can provide personalized learning and guidance for art-normal students and improve the learning effect by recommending learning resources and works suitable for their needs and levels.